Use of macrolides in lung diseases: recent literature controversies - Luiz Vicente Ribeiro Ferreira da Silva Filho; Leonardo Araujo Pinto; Renato T. Stein (Elsevier, 2015)
Objective: To review the mechanisms of action of macrolides in pediatric respiratory diseases and their clinical indications. Sources: Review in the PubMed database, comprising the following terms in English: "macrolide and asthma"; "macrolide and cystic fibrosis"; "macrolide bronchiolitis and viral acute"; "macrolide and bronchiolitis obliterans" and "macrolide and non-CF bronchiectasis". Summary of the findings: The spectrum of action of macrolides includes production of inflammatory mediators, control of mucus hypersecretion, and modulation of host-defense mechanisms. The potential benefit of macrolide antibiotics has been studied in a variety of lung diseases, such as cystic fibrosis (CF), bronchiectasis, asthma, acute bronchiolitis, and non-CF bronchiectasis. Several studies have evaluated the benefits of macrolides in asthma refractory to therapy, but the results are controversial and indications should be limited to specific phenotypes.In viral bronchiolitis, there is no consistent benefit in acute conditions, although recent data have shown an effect in recurrent wheezing prevention. In patients with CF results are also contradictory, but the consensus states there is a small clinical benefit, especially for patients infected with P. aeruginosa. There was also no positive action of macrolides in patients with post-infectious bronchiolitis obliterans. Children with non-CF bronchiectasis seem to have clear benefits regarding the use of macrolides, which showed clinical advantages in parenchyma protection and lung function. Conclusions: The long-term use of macrolides should be limited to highly selected situations, especially in patients with bronchiectasis. Careful evaluation of the benefits and potential damage are tools for their indication in specific groups. Resumo: Objetivo: revisar os mecanismos de ação de macrolídeos em doenças respiratórias pediátricas e as suas indicações clínicas. Fonte de dados: revisão na base de dados Pubmed, compreendendo os termos em inglês referente ao tema básico. Síntese dos dados: O seu espectro de ação estende-se desde a produção de mediadores inflamatórios, o controle da hipersecreção de muco e modulação de mecanismos de defesa do hospedeiro. O potencial benefício dos antibióticos macrolídeos foi estudado em doenças pulmonares como a fibrose cística, as bronquiectasias, a asma, a bronquiolite aguda e as bronquiectasias não ligadas à fibrose cística. Diversos estudos avaliaram os benefícios dos macrolídeos na asma resistente a terapia, porém, os resultados são controversos e as indicações devem ser limitadas a fenótipos específicos. Na bronquiolite viral não há benefícios consistentes nos quadros agudos, embora dados recentes mostrem um efeito na prevenção de sibilância recorrente. Em pacientes com fibrose cística os resultados também são contraditórios, mas o consenso é de que há um pequeno benefício clínico, especialmente para os pacientes infectados por P. aeruginosa. Também não foi observada ação positiva dos macrolídeos em pacientes com bronquiolite obliterante pós-infecciosa. Crianças com bronquiectasias não relacionadas à fibrose cística parecem ter claros benefícios em relação ao uso de macrolídeos, os quais mostraram vantagens clínicas, de proteção ao parênquima e na função pulmonar. Conclusões: O uso em longo prazo de macrolídeos deve ser limitado a situações altamente selecionadas, especialmente em pacientes com bronquiectasias. Avaliação cuidadosa dos benefícios e potenciais danos são ferramentas para indicação em grupos específicos. Keywords: Pulmonary diseases, Macrolides, Inflammation, Children, Adolescents, Palavras-chave: Doenças pulmonares, Macrolídeos, Inflamação, Crianças, Adolescentes